Development of a mobile-based health management application for men in andropause - Young Sook Lim; Sun Jung Park (Journal of Men's Health)
This study attempted to develop a mobile-based health management application targeting middle-aged men experiencing andropause, with the aim of allowing them to prevent and continuously manage health issues that may arise during the experience of andropause. The mobile web-based andropause health management program focused on providing a wide range of information and enhancing self-management by integrating various sources of information. Additionally, the app was developed based on the Android OS (used in domestic smartphones), enabling comprehensive information access anytime and anywhere in daily life, and offering various self-measurement features to facilitate effective self-management for individuals experiencing andropause. Currently, existing andropause management apps are designed for women, making this study’s program unique as it is developed for middle-aged men. Furthermore, by connecting various psychological counseling programs, this application can be utilized as a resource for mental health management, allowing for shortened intervention times and flexible, accessible interventions when necessary. While this andropause app for men was developed through user satisfaction surveys, it is necessary to conduct a larger study to test the effectiveness of the andropause health management program for middle-aged men.